Kepemimpinan Ki Hadjar Dewantara dalam Manajemen Dakwah - Moh. Muafi Bin Thohir (Institut Agama Islam Syarifuddin Lumajang, 2021)
The Leadership as a management concept in organizational life has a very strategic position that is always applied in organizational life. Like the concept of Javanese leadership conceptualized by Ki Hadjar Dewantara in his Javanese philosophy, namely Ing ngarsa sung tuladha, Ing madya mangun karsa, Tutwuri handayani which means in front of being an example, in the middle giving guidance, behind giving encouragement. The three philosophies have a relationship between humans, namely the relationship of influence and exemplary between the leader and its members because it is influenced by the authority of the leader. The leadership relationship in da'wah management will lead to the ideal figure in the da'wah organization. because the understanding of da'wah management in general is a scientific concept that focuses on the management of da'wah organizations in which the organization requires a role model leader in accordance with Islamic teachings. This study uses a descriptive-analytic research method with a socio-historical-anthropological approach. This approach is carried out to review a problem from the point of view of history with a system of thinking that follows the rules of logic freely and deeply. The concept of the Javanese philosophy of Ki Hadjar Dewantara (Ing ngarsa sung tuladha, Ing madya mangun karsa, Tutwuri handayani) is a Javanese leadership concept which can also be called plenary leadership or overall leadership which includes all its exemplary aspects by setting a good example for its members. Ing Ngarsa Sung Tulodo in front set the example. Ing Madya Mangun Karsa is in the middle of providing motivation. Tutwuri Handayani in the back gave encouragement. Keywords: Da’wah Management, Javanese, Leadership